Effect of Passive Ultrasonic Irrigation on Apical Extrusion of Irrigating Solution - Tasdemir, Tamer; Er, Kursat; Celik, Davut; Yildirim, Tahsin (European Journal of Dentistry, 2008)
Objectives: To determine the influence of passive ultrasonic irrigation (PUI) on apical extrusion of irrigating solution.Methods: Twenty freshly extracted maxillary and mandibular incisors with single straight root canals were instrumented with ProTaper rotary files. During final irrigation, the root canals were filled with 2.5% sodium hypochlorite (NaOCl) solution and PUI was performed with a piezoelectronic unit. A stainless steel instrument (size 15) was inserted into the root canal and the irrigant was ultrasonically activated for one minute. This sequence was repeated three times, resultingin a total PUI time of three minutes. The volume of extruded irrigant was measured by Pipetman pipettes. The data were statistically analyzed with the Mann-Whitney U test.Results: The mean volume of apical extruded irrigant was 2.15 L for the PUI group and 14 L forthe control group. The experimentalgroup extruded significantly smaller amounts of irrigant than the control group (P<.05).Conclusions: The PUI procedure as a final irrigation was associated with less apical extrusion of the irrigating solution. (Eur J Dent 2008;2:198-203)
Keywords: Apical extrusion; Passive; Ultrasonic; Irrigation